Hey!
The first step to solving this equation would be to rearrange it. It's better to rearrange it so that it is easier to solve.
Original Equation :
−x = 4 − 3x + 6
New Equation {Changed by Rearranging} :
-x = -3x + 4 + 6
Next we would group our like terms.
We can see that both 4 and 6 are whole numbers and can be added easily, so we'll start by grouping those like terms first.
Old Equation :
-x = -3x + 4 + 6
New Equation {Created by Grouping Like Terms} :
-x = -3x + 10
Now we add 3x to both sides to get rid of the -3x on the left side of the equation.
Old Equation :
-x = -3x + 10
New Equation {Changed by adding 3x to Both Sides} :
-2x = 10
Almost done! Our equation is one step closer to being solved.
Next, we will divide both sides by 10 to get x on its own.
Old Equation :
-2x = 10
New Equation :
x = 5
Our equation can now no longer be simplified any farther. Therefore, it is officially solved!
The value of x in the equation −x = 4 − 3x + 6 is x = 5.
Hope I helped!
- Lindsey Frazier ♥